Juridical Review of Midwife Practices and Authorities in Providing Midwifery Services Based on Presidential Regulation No. 82 of 2018 concerning Health Insurance - Nur Hidayah; Samuri Samuri (SOEPRA, 2022)
Abstract: Midwives are health workers who have an important and strategic position, especially in reducing the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR), as well as playing a role in the national health system, namely BPJS. The hope is that if Independent Practicing Midwives can directly network with BPJS it will maximize Midwifery services to people who have BPJS cards, especially for mothers who are going to give birth, pregnancy checks at health services in village midwives who are in their respective villages. This study aims to review the practice and authority of midwives in providing midwifery services based on Presidential Decree No. 82 of 2018 concerning health insurance. using a statutory approach, namely examining all laws and regulations related to the issues to be discussed. Hierarchically, the laws and regulations related to midwifery practice as regulated in Presidential Decree No. 82 of 2018 concerning health insurance are not by the above laws and regulations, namely Law No. 4 of 2019 regarding the regulation of independent midwife practice which must network with health facilities that have support, while from the laws and regulations of the Midwifery Law that Midwife Practices are given the authority to practice independently.Keywords: juridical review, midwife practice, bpjs Abstrak: Bidan merupakan salah satu tenaga kesehatan yang memiliki posisi penting dan strategis terutama penurunan Angka Kematian Ibu (AKI) dan angka kesakitan dan kematian Bayi (AKB), serta ikut berperan dalam system kesehatan nasional yaitu BPJS. Harapannya apabila Bidan Praktek Mandiri langsung bisa jejaring dengan BPJS akan lebih  memaksimalkan pelayanan Kebidanan kepada masyarakat yang mempunyai kartu BPJS khususnya untuk ibu yang akan melakukan persalinan, pemeriksaan kehamilan dipelayanan kesehatan di bidan desa yang berada di desa mereka masing - masing.  Penelitian ini bertujuan untuk mengetahui tinjauan praktik dan kewenangan bidan dalam pemberian pelayanan kebidanan berdasarkan perpres no 82 tahun 2018 tentang jaminan kesehatan. menggunakan pendekatan perundang‐undangan(statute approach), yaitu menelaah semua peraturan perundang undangan yang terkait denganpermasalahan yang akan dibahas. Secara hirarki peraturan perundang – undangan terkait praktik kebidanan yang diatur dalam Perpres No 82 Tahun 2018 tentang jaminan Kesehatan  tidak sesuai dengan peraturan perundangan diatasnya yaitu Undang – Undang No 4 Tahun 2019 terkait pengaturan Praktik Bidan Mandiri yang harus jejaring dengan fasilitas Kesehatan yang memiliki penunjang, sedangkan dari peraturan perundangan Undang – Undang Kebidanan bahwa Praktik Bidan diberikan kewenangan untuk Praktik Mandiri.Kata Kunci: tinjauan yuridis, praktik bidan, bpjs